2021
DOI: 10.1097/corr.0000000000001825
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Urgent Care Centers Restrict Access for Patients with Medicaid Insurance Based on Policy and Location

Abstract: Background As the urgent care landscape evolves, specialized musculoskeletal urgent care centers (MUCCs) are becoming more prevalent. MUCCs have been offered as a convenient, cost-effective option for timely acute orthopaedic care. However, a recent “secret-shopper” study on patient access to MUCCs in Connecticut demonstrated that patients with Medicaid had limited access to these orthopaedic-specific urgent care centers. To investigate how generalizable these regional findings are to the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…The existing literature 3 , 4 indicates that MUCCs operate on a profit-driven model, having clinic policies in place that ensure a certain payer mix. Therefore, care at MUCCs may be unavailable to patients who are most in need of cost savings: the uninsured and underinsured.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The existing literature 3 , 4 indicates that MUCCs operate on a profit-driven model, having clinic policies in place that ensure a certain payer mix. Therefore, care at MUCCs may be unavailable to patients who are most in need of cost savings: the uninsured and underinsured.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Multiple studies have confirmed that a high percentage of MUCCs do not accept Medicaid insurance. 3 , 4 Urgent care centers are not subject to the Emergency Medical Treatment and Active Labor Act and therefore are legally able to screen patients based on their perceived ability to pay. Our findings suggest that a practice’s policy of Medicaid acceptance, median household income per zip code, and Medicaid reimbursement for a level 3 visit are associated with visit charges at MUCCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 ] MUCCs also increase access to specialty providers, as many MUCCs are owned and operated privately by orthopedic surgeons. [ 2 ] Accessing orthopedic specialists in the ED setting can be challenging and approximately 25% of visits to the ED are due to diseases of the musculoskeletal system or musculoskeletal injuries. [ 3 , 4 ] However, many MUCCs restrict access to patients based on insurance type which may limit care options for patients.…”
Section: Introductionmentioning
confidence: 99%